Teknik Koreksi Posisi dan Bentuk Objek Citra dalam Basis Waktu-Bilangan Gelombang - Is Mardianto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
In the case of radar imagery, the image is the result of convolution between the wave source and the reflection coefficient of the object, which of them is the amount of electrical conductivity and dielectric constant of the object. Image is produced from the concept of scattering, where the absence of scattering events will not produce radar image. The image of the measurement results usually do not represent the position and shape of the actual object condition. To restore the image to the actual condition, a proper technique is needed.This study presents the technique of image correction in the base period and the number of waves (T-K), on the conditions of the object in the form of sloping soil layers and diffraction object in the form of metal that is round. Image correction on the basis of T-K is conducted by performing Fourier transformation on the original image (wave field F (t, k)) in the space dimension x to dimension k that generates a field new wave F (t, k). Then, wave field F (t,k) will be corrected for each wave number by converting it first into a new wave field Q (τ,k), then the wave field Fourier transformed to obtain the corrected section q (τ,x)Results of image correction on the basis of the T-K gives the results of the position and shape of the image that is appropriate based on the actual conditions. This can be ascertained because of the imagery used is a synthetic image of the position and the initial condition is set and known in advance.